Biology and consumptian o! predalar Cal/ida sp. (Coleoptera: Carabidae) reared onAnticarsia genimatalis Hübnor, 181 - Corrêa-Ferreira, Beatriz Spalding; Pollato, Sandra Lúcia Bocchi (Pesquisa Agropecuaria Brasileira, 2013)
The biology and consumption ol Cal/ida sp. was studied under laboratory conditions (260C ± 20C, temperature, 60% ± 10% RH) in Londrina, PR, Brazil, Developmental time from lhe egg through adult was 32 days, with lhe highest morlality in lhe third instar larvae (26,7%). As to larval weight, II was observed lhat lhe highest increasing also oecurred in lhe third instar (7.7 mg). The mean otto total consumplion ol Cal/ida sp. during lhe larval period was 65.6 ulilizing the second instar larva ol Anticarsia gemrnatalis Hübner, 1818. Third instar larvae ingested 83.3% of lhe total available larva supplied. The mean daily consumplion 01 ditierent Iarvae was 0.0, 1.9 and 6.2 larvae lor te first second and third instar, respectively. Adulta o! Cal/ida sp. ingest a daily average ol 48.1 small larvae, showing preference lo second-instar larvae ol A. gemmatalis. Considering that adult longevity averaged 49.2 days, lhe potendal of consumption during this period is significalive.
Keywords: nutrition; biological control; biology; predation.